2022
DOI: 10.47577/tssj.v33i1.6977
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the pandemic crisis on employment in the context of urbanization

Abstract: The level of economic and social development of a country is closely linked to the degree of urbanization. Continuous urbanization will bring new opportunities for and challenges to sustainable development, which is closely correlated with the general level of economic and social development. Thus, the global urbanization trend has been accompanied by changes in employment, representing both a goal and a means of sustainable development at the level of all the branches of national economies. A major test for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Although Constanta County is the most economically developed county in the South-East Region, both decision-makers and investors face the challenge of balancing the benefits of economic growth against the mitigation of the pressure on the environment (Vintilă et al, 2017;Stan et al, 2021a;Stan et al, 2021b). Moreover, there are vulnerable social groups and marginalized communities in the county in need of social projects to alleviate problems and reduce the rural-urban imbalance in terms of employment opportunities (Stan, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Although Constanta County is the most economically developed county in the South-East Region, both decision-makers and investors face the challenge of balancing the benefits of economic growth against the mitigation of the pressure on the environment (Vintilă et al, 2017;Stan et al, 2021a;Stan et al, 2021b). Moreover, there are vulnerable social groups and marginalized communities in the county in need of social projects to alleviate problems and reduce the rural-urban imbalance in terms of employment opportunities (Stan, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that there is a direct relationship between turnover and real estate market's labor force (Cain, Springer and Worzala, 2020), the real estate expansion increasing labor demand and alleviating unemployment (Gong et al, 2022), however, turnover depends on the market (Stan, 2021b). The quantity of labor force is determined by the economic opportunities found in urban and rural areas (Stan, 2022a), but also by economic agents whose role is to invest in human capital, in relation to production and economic growth (Wijaya et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%